Effect of Stenochlaena palustris extract on circulating endothelial cellsMarmota caligata induced fever - Eko Suhartono; M. Bakhriansyah; Rini Handayani (Universitas Gadjah Mada, 2010)
Fever is increased temperature regulation of the body. In the process is according indirect which increased of free radicals, as anion superoxide (•O2) and will trigger oxidative stress happened. Oxidative stress will effect in endothelial damaged. A celluler marker of damage the endothelium is increased number of Circulating Endothelial Cells (CEC). The aim of this research is to valuated the influence of watery plant kalakai extract (Stenochlaena palustris)to number of Circulating Endothelial Cells in Marmota caligata had been fever and to calculated the average of CEC. The research is true experimental study, with Posttest-Only with Control Group Design, with 2 control group and 5 treatments group of each 4 Marmota caligata. The CEC is measured by Hladovec method. Data was analyzed by using Kruskal-Wallis test with confidence rate at 95 %. The analyzed results got p = 0.001 (p < 0.05) means there be a significant different between treatment group. From the result, can be conclude that the present of watery plant kalakai extract is decreasing CEC in plasma of Marmota caligatafever induced.